1983
DOI: 10.1084/jem.157.5.1646
|View full text |Cite
|
Sign up to set email alerts
|

Accessory cells in murine Peyer's patch. I. Identification and enrichment of a functional dendritic cell.

Abstract: Previous studies have suggested that in vitro and in vivo immune responses are defective in Peyer's patch (PP) as a result of a deficiency in accessory cell number or function. However, we report here that enzymatic dissociation of PP does release a cell population with accessory activity in oxidative mitogenesis, i.e., the proliferation of periodate-modified T cells. The accessory activity present in PP is quantitatively similar to that of spleen. Accessory function is mediated by a cell type(s) that has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…In these and several other studies DC were reproducibly the most potent stimulators of allogeneic MLR when compared to macrophages. The results of this study are in agreement with those of Spalding et al [34], who demonstrated the stimulatory ability of mouse splenic DC in allogeneic MLR. Similar work on DC from mouse intestinal lamina propria and pig Peyer's patches [21,20,27,40], as well as studies of DC from the human colonic lamina propria demonstrated the presence of cells with potent stimulatory activity in the allogeneic MLR.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In these and several other studies DC were reproducibly the most potent stimulators of allogeneic MLR when compared to macrophages. The results of this study are in agreement with those of Spalding et al [34], who demonstrated the stimulatory ability of mouse splenic DC in allogeneic MLR. Similar work on DC from mouse intestinal lamina propria and pig Peyer's patches [21,20,27,40], as well as studies of DC from the human colonic lamina propria demonstrated the presence of cells with potent stimulatory activity in the allogeneic MLR.…”
Section: Discussionsupporting
confidence: 83%
“…Professional APC are characterized by their constitutive high levels of major histocompartibility complex (MHC) class II expression, poor phagocytic ability, lack of sIg and Fc receptors, weak adherence to solid supports [34] and their ability to stimulate primed T cell proliferation in an antigen specific manner [29]. Studies have clearly shown that peritoneal macrophages are highly proliferating progenitors for functional DC [24,28].…”
mentioning
confidence: 99%
“…These include different types of conventional APCs like dendritic cells (17)(18)(19)(20)(21)(22)(23)(24)(25), macrophages (26,27), and B cells (28) along with other putative APCs such as intestinal epithelial cells (29). We have found that the APC responsible for the presentation of oral OVA to both CD4 ϩ and CD8 ϩ T cells in the GALT is of bone marrow origin because T cell proliferation was evident only in chimeric mice in which the bone marrow-derived compartment expressed the correct MHC haplotype (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The current accepted concept is that DC comprise three distinct subpopulations, including two within the myeloid lineage (LC and interstitial DC) and one within the lymphoid lineage [107]. DC can be classified on the basis of their tissue location as: interdigitating reticulum cells in the dome and inter follicular areas (IFA) of lymphoid organs [59,168]; Veiled cells (non lymphoid DC) in afferent lymph [61,138]; Blood DC when in circulation [136,166]; Langerhans cells in the epidermis [150]; dermal DC when found in the dermis of the skin [142,146]; follicular DC, in B cell areas (follicles) of the spleen, lymph nodes and Peyer's patches [128]; and interstitial DC, in the interstitial connective tissues of non-lymphoid organs [45]. Tissues from which DC have been isolated are summarized in Table 1.…”
Section: Dendritic Cell Classificationmentioning
confidence: 99%